GoTradeSeafood.com: Reeling in the Big Catch - Stoller, Gregory L. (Senate Hall, 2003)
In December, 2000, the father-and-son team of Jerry and Joshua ten Brink are contemplating the future for their 17-month old venture, GoTradeSeafood.com. Funded up to now primarily by family funds, GoTradeSeafood.com provides an electronic medium through which to buy and sell seafood. At the time of the case, the site's database is over 2,000 members strong, supports seafood trades and exchanges of approximately $130 million per month, and each day attracts over 1,000 unique visitors. Based on the company's recent financial statements, the management team believes it has a greater-than-average chance of meeting its profitability target by mid-2001 - a date only six months behind its original schedule. The case contains a full-length business plan and challenges the reader to articulate an action plan in the areas of marketing, pricing, product and service adoption, and competitive responses. Students are also asked to critique the strengths and weaknesses of the business plan, assess its suitability for the venture capital community, and compare the company to its other "dot com" brethren.
Keywords: entrepreneurship|business planning